0536 Response to Upper Airway Stimulation in Older Adults with Moderate to Severe Obstructive Sleep Apnea. (27th April 2018) - Strollo, P J; Withrow, K; Schell, A; Soose, R; Mehra, R; Schwab, R; Strohl, K; Doghramji, K
Abstract: Introduction: The 5-year follow up data from the STAR trial suggested that older adults may have a better response to Upper Airway Stimulation (UAS) than younger individuals. We aimed to test this hypothesis in participants enrolled in the ADHERE Registry (Adherence and Outcome of UAS for OSA International Registry) by examining the differential impact of age on the self-reported sleepiness, Apnea Hypopnea Index (AHI), and device adherence to therapy at one-year post implant. Methods: Study design: multicenter prospective and retrospective observational cohort study. Participants who had undergone UAS implantation were eligible for enrollment. Baseline measures included demographic data, Epworth Sleepiness Scale (ESS) and sleep study data. Outcome measures included change in ESS, change in AHI and objective adherence to UAS among younger (age less than 65 years) compared to older participants (age greater than or equal 65 years) in the ADHERE Registry. Results: Baseline measures : Younger Adults (n = 271): Age 57.7 ± 7.6 yrs., 84% male, 97% Caucasian, BMI 29.5 ± 3.8, ESS 12.6 ± 5.3, AHI 36.5 ± 16.2. Older Adults (n = 155): 71.4 ± 4.9, 73% male, 97% Caucasian, BMI 28.8 ± 4.0, ESS 10.4 + 5.7, AHI 36.7 ± 14.9. Outcome measures : Younger Adults (n =271): AHI post-titration 10.5 ± 13.3, AHI at 12 months 11.8 ± 13.3, ESS post-titration 8.2 + 5.0, ESS at 12 months 7.1 + 4.9, Therapy usage post-titration 6.3 ± 2.4 hrs./ night, Therapy usage at 12 months 5.4 ± 2.1 hrs / night. Older Adults (n = 155): AHI post-titration 8.7 ± 11.5, AHI at 12 months 7.7 ± 5.8, ESS post-titration 6.4 ± 5.0, ESS at 12 months 5.6 ± 3.9, Therapy usage post-titration 6.7 ± 2.0 hrs. / night, Therapy usage at 12 months 6.3 ± 2.0 hrs / night Conclusion: Older ADHERE registry participants were less sleepy at baseline compared to younger participants with similar AHI and BMI values. ESS improved in both groups. Objective adherence to UAS was significantly better in the older population. Support (If Any): Inspire Medical Systems.